Efektifitas Caring Perawat (Maintaining Belief) Terhadap Penurunan Kecemasan Pre-operasi Appendiktomi : The Effectiveness of Nurse Caring (Maintaining Belief) on Reducing Pre-Operational Anxiety Appendectomy - Suhartini, Tini (Dohara POAJ, 2022)
Introduction: Anxiety faced by patients when going to surgery includes fear of pain, fear of physical changes, and fear that the operation will fail and this anxiety can cause delaying or canceling the operation. Anxiety is an emotional response to an assessment that describes a state of worry, anxiety, fear, and restlessness accompanied by various life situations as a disease disorder. In the management of nursing care in preoperative patients who experience anxiety, nursing interventions are needed, one of which is caring. Caring is a behavior or action taken to provide a sense of physical and emotional security to others sincerely. The purpose of caring behavior is to provide physical care by paying attention to emotions while increasing a sense of security by showing concern, feelings of empathy, and love. The nurse's caring attitude towards the client in providing nursing care by caring for the client with sincerity, sincerity, and full of love, both through communication, providing support, and direct action Purpose: This study aims to determine the effectiveness of nurse caring (maintaining belief) given to preoperative appendectomy patients and its effect on reducing anxiety Methods: The research used was quasi-experimental (quasi-experimental) using two groups of subjects with a control group (Nonequivalent Control Group Design). Measurements were carried out before and after treatment. Using a non-randomized pretest and posttest group design approach. The total population was 52 patients and the entire population was sampled (total sampling) and divided into 2 groups of 26 patients each Results: In the group of caring nurses (maintaining belief) there was a decrease in anxiety in patients pre-operative appendectomy from heavy to moderate and from moderate to mild. From the results of the Wilcoxon test that on average there is a difference with a p-value (0,000 <0,05). While in the control group there was a slight decrease in anxiety in appendicectomy pre-operative patients from severe to moderate. From the results of the Wilcoxon test that the average is different from the p-value (0,317 <0,05). Discussion: There is a difference in the average decrease in the anxiety of appendectomy pre-operative patients, both in respondents who do care nurses (maintaining belief) and those who do not, by doing caring nurses (maintaining belief) managed to reduce the anxiety felt by pre-operative appendectomy patients.